Some verbs related to the object and prepositional clauses - Al-Salamat, Atef Abdulkarim (Journal of Humanities & Social Sciences, 2020)
This study aims to give knowledge about some related verbs as there are few studies about this subject particularly in the object and prepositional clauses, the researcher studied some belonging or related (object and prepositional clause), and then the research explained that the object and prepositional clause do not come in advance in the Holy Qur’an unless there is a rhetorical reason required by the anecdotal context, and then if it is mentioned or deleted or brought in advance, it comes as a natural result for the anecdotal context which is found in the Holy Qur’an. If it is mentioned or deleted or advanced in a particular verse, so the scholar must take into consideration the previous verses to conclude that the advancement has a relation with those verses.If it is seen that in deleting or advancing the object has an expansion to the poet or the writer, for that is truly applied in the Holy Qur’an at all, so it is better in studying the advancement of the object or prepositional clause with the atmosphere of the event and the story, and not to adhere to the one-sentence system, which is better to explain the rhetorical images that are contemplated from this advancement.
Keywords: some verb related; object; prepositional clause; Contexts